(untitled) (Clinics, 2011)
Cellular energy metabolism is one of the main processes affected during the transition from normal to cancer cells, and it is a crucial determinant of cell proliferation or cell death. As a support for rapid proliferation, cancer cells choose to use glycolysis even in the presence of oxygen (Warburg effect) to fuel macromolecules for the synthesis of nucleotides, fatty acids, and amino acids for the accelerated mitosis, rather than fuel the tricarboxylic acid cycle and oxidative phosphorylation. Mitochondria biogenesis is also reprogrammed in cancer cells, and the destiny of those cells is determined by the balance between energy and macromolecule supplies, and the efficiency of buffering of the cumulative radical oxygen species. In glioblastoma, the most frequent and malignant adult brain tumor, a metabolic shift toward aerobic glycolysis is observed, with regulation by well known genes as integrants of oncogenic pathways such as phosphoinositide 3-kinase/protein kinase, MYC, and hypoxia regulated gene as hypoxia induced factor 1. The expression profile of a set of genes coding for glycolysis and the tricarboxylic acid cycle in glioblastoma cases confirms this metabolic switch. An understanding of how the main metabolic pathways are modified by cancer cells and the interactions between oncogenes and tumor suppressor genes with these pathways may enlighten new strategies in cancer therapy. In the present review, the main metabolic pathways are compared in normal and cancer cells, and key regulations by the main oncogenes and tumor suppressor genes are discussed. Potential therapeutic targets of the cancer energetic metabolism are enumerated, highlighting the astrocytomas, the most common brain cancer.